The Influence of Shoppe on Consumer Behavior: A Case Study in Malaysia - Sofiya, Nur Ainin; Syauqina, Nur Dini; Fadhilah, Nur; Fatihah, Nur; Alam, Aaliya; Upadhyay, Adarsh (AIBPM Publisher, 2023)
‘9 out of 10 online’ indicates that Malaysia’s e-commerce industry has risen steadily throughout Southeast Asia. The increase in the number of Shopee apps in the second quarter of 2021, marks Shopee as a leading Malaysian e-commerce market. Shopee provides a good value, the best quality, convenience and security when consumers experience the app. This paper aims to look into factors that influence consumers' behaviours towards online shopping using the Shopee app. This paper also assesses customer satisfaction regarding the service that had been provided. A total of 100 respondents of Shopee users participated in the online survey via Google Form. From the analysis, the results depict the necessity of quality products, reliability, convenience and product price as good indicators of customer satisfaction that may lead to behavioural intention. These findings provide new insight into consumer behaviour towards Shopee.